Does crossing a moral line justify collective means? Explaining how a perceived moral violation triggers normative and nonnormative forms of collective action - Pauls, Inga L.; Shuman, Eric; Zomeren, Martijn; Saguy, Tamar; Halperin, Eran (European journal of social psychology, 2022)
In three studies conducted in the United States, we examined whether a perceived moral violation motivates willingness to engage in normative and more radical collective action. Using value‐protection and identity‐formation models, we explored whether increased endorsement of moral convictions and relevant opinion‐based group identification could explain such effects. Study 1, using the “travel ban” for Muslims as the focal issue, experimentally found that a strong violation, compared to a weak violation, increased normative and nonnormative collective action, moral convictions and opinion‐based group identification. Study 2 replicated these results in a longitudinal design and supported a mediating effect of increased endorsement of moral convictions and opinion‐based group identity. Study 3 used a real‐world violation (the United States’ withdrawal from the Paris climate agreements) to replicate the findings cross‐sectionally. We conclude that a perceived moral violation motivates normative and nonnormative collective action because the violation makes one's moral conviction and opinion‐based group identification more salient.